2017
DOI: 10.1038/s41598-017-01169-6
|View full text |Cite
|
Sign up to set email alerts
|

COX-1/PGE2/EP4 alleviates mucosal injury by upregulating β-arr1-mediated Akt signaling in colitis

Abstract: COX-1/PGE2 is an important protective mediator in ulcerative colitis (UC). β-arrestin1 (β-arr1), which acts as a scaffold protein, is involved in PGE2-mediated signaling pathways. However, the interaction between PGE2 and β-arr1 in maintaining mucosal barrier integrity remains unexplored. In this study, we demonstrated that COX-1 and PGE2 were significantly decreased, and EP4 mRNA was downregulated in both UC patients and mice during the injury phase. PGE2 treatment was found to alleviate mucosal injury and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…UC is characterized by inflammation, homeostasis disruption, and epithelial barrier damage in the intestinal tract, and DSS is a well-established agent to induce experimental colitis that is phenotypically similar to UC in humans [29]. DSS-induced colitis is of reasonable reproducibility and of great value for investigating the efficacy of anticolitis agents.…”
Section: Discussionmentioning
confidence: 99%
“…UC is characterized by inflammation, homeostasis disruption, and epithelial barrier damage in the intestinal tract, and DSS is a well-established agent to induce experimental colitis that is phenotypically similar to UC in humans [29]. DSS-induced colitis is of reasonable reproducibility and of great value for investigating the efficacy of anticolitis agents.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is conflicting evidence regarding the level of PGE2 during intestinal inflammation. Peng et al showed that PGE2 was significantly decreased in the colon of patients with UC, as well as in DSS colitis (34), while Maseda et al…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study revealed an essential role of EP4 in the differentiation of wound healing macrophages in the intestine, which 20 can be targeted as a new treatment strategy for IBD. Future work on the expression of EP4 and CD206 in macrophages based on the genetic information together with tracking long-term 34 therapeutic responses might provide further valuable information to develop patient specific therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of mPGES-1 during intestinal inflammation has not been as deeply studied. mPGES-1-deficient animals are partially protected from dextran sulfate sodium (DSS)-induced colitis (35), and PGE 2 treatment alleviates mucosal injury and induces EP4 expression during DSS-induced colitis in WT mice (39). These data suggest a protective role of mPGES-1-derived PGE 2 during intestinal injuries, but the mechanisms describing how mPGES-1 competence on tissue damaging cells like lymphocytes affects colitis is unknown.…”
Section: Discussionmentioning
confidence: 99%